2018
DOI: 10.1590/s1806-37562017000000443
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tuberculosis: diabetes, smoking, alcohol use, and the use of other drugs

Abstract: Tuberculosis continues to be a major public health problem. Although efforts to control the epidemic have reduced mortality and incidence, there are several predisposing factors that should be modified in order to reduce the burden of the disease. This review article will address some of the risk factors associated with tuberculosis infection and active tuberculosis, including diabetes, smoking, alcohol use, and the use of other drugs, all of which can also contribute to poor tuberculosis treatment results. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
1
46

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 57 publications
5
141
1
46
Order By: Relevance
“…In Montes Claros-MG, it was observed that of 661 patients with tuberculosis, 60.4% of the patients were male [16]. This predominance of males has been associated with cultural issues, due to alcohol and/or tobacco consumption, which may compromise immunity and nutritional status, and thus increase the likelihood of acquiring tuberculosis [17].…”
Section: Resultsmentioning
confidence: 99%
“…In Montes Claros-MG, it was observed that of 661 patients with tuberculosis, 60.4% of the patients were male [16]. This predominance of males has been associated with cultural issues, due to alcohol and/or tobacco consumption, which may compromise immunity and nutritional status, and thus increase the likelihood of acquiring tuberculosis [17].…”
Section: Resultsmentioning
confidence: 99%
“…Data point out to the impact of diabetes on the immune system, favoring the bacillus survival 27 . Diabetes causes increased susceptibility to TB through several mechanisms, including hyperglycemia and cellular insulinopenia, which have indirect effects on macrophage and lymphocyte function 27,28 . Diabetes is Mutations in the gyrA gene were also found in all the 41 samples, constituting the main mechanism of resistance to FQ, with specific mutations at codons 89, 90, 94 and 95.…”
Section: Discussionmentioning
confidence: 99%
“…Com relação à raça, os dados obtidos no presente estudo que evidenciam maior prevalência de TB na população branca (74,2%) divergem do estudo de Ferraz (14) que encontrou maior prevalência entre a população negra (76,7%), tal achado decorre, pois nos municípios estudados há predominância da população branca, pelo censo IBGE 2010, 84% da população de SC se declarara branca (21)(22) .…”
Section: Resultsunclassified
“…Quanto aos aspectos individuais, o uso de drogas, a ocorrência de outras doenças, www.ufsj.edu.br/recom -7 principalmente as crônicas são identificadas como contribuindo para a não adesão ao tratamento (22) .…”
Section: Resultsunclassified